Additive effect of radiosensitization by 2‐deoxy‐D‐glucose delays DNA repair kinetics and suppresses cell proliferation in oral squamous cell carcinoma. (16th July 2017) - Kawata, Mayumi; Ogi, Kazuhiro; Nishiyama, Koyo; Miyamoto, Sho; Nakagaki, Takafumi; Shimanishi, Makoto; Miyazaki, Akihiro; Hiratsuka, Hiroyoshi
Abstract : Background: It has well known that, compared to normal cells, tumor cells have a different manner of energy metabolism, which influences the sensitivity of radiotherapy. However, whether inhibition of glycolysis enhances the efficacy of radiotherapy is a matter of debate in oral squamous cell carcinoma (OSCC). The aim of this study was to characterize whether the combination of radiotherapy with the glucose inhibitor 2‐deoxy‐D‐glucose (2‐DG) affected DNA repair kinetics. Methods: To compare the synergistic effect of 2‐DG, we examined the cell survival after treatment with radiation, 2‐DG, and a combination of the two in five OSCC cell lines and one lip fibroblast cell line, determined using clonogenic survival assay. Changes in the protein levels of DNA repair kinetics such as PARP, Rad51, and Ku‐70 were analyzed by Western blotting. Then, using one of the five OSCC cell lines, we assessed the inhibition of xenograft tumor growth in vivo. Results: We found that 2‐DG with radiation induced significant inhibition of cell proliferation in cell line SAS ( P <.01, one‐way ANOVA). Radiation treatment was associated with decreased expression of the DNA repair markers. In additional, combinational treatment with 2‐DG and radiation significantly inhibited the xenograft tumor growth compared to the control ( P <.05), and treatment with 2‐DG or radiation alone. Conclusions: Our study suggests that 2‐DG has synergistic cytotoxic effects when combined with radiotherapy, which might lead to the design of an effective metabolic target therapy in vitro and in vivo.